Unemployment of immigrants and natives over the business cycle: evidence from the Austrian labor market - Nora Prean; Karin Mayr (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2012)
We analyze differences in unemployment between natives and immigrants over the business cycle. Using matched employer-employee data for Austria, we find that immigrants' unemployment rate and flows into and out of unemployment are significantly more sensitive to labor market shocks than those of comparable natives. This is particularly true for immigrants from outside the European Economic Area. According to existing theory, a greater variability in the employment of immigrants can be due to a selection of immigrant workers into specific industries or temporary jobs. However, we do not find this confirmed in our data.
Keywords: J64; J61; 330; Unemployment rate; Immigration; Guestworker; Immigrant Labor